PERBEDAAN LEVEL RERATA KEKUATAN OTOT DASAR PANGGUL SEBELUM DAN SETELAH PERSALINAN SPONTAN PADA KELOMPOK INKONTINENSIA URIN DAN KELOMPOK NORMAL - Bobby Indra Utama; Hasni Kemala Sari; Hafni Bachtiar (Andalas Obstetrics And Gynecology Journal, 2017)
Trauma to the pelvic floor during delivery is now recognized as a major etiological factor against PFM disorders such as urinary incontinence, pelvic organ prolapse and fecal incontinence. This study was conducted to analyze the differences in mean levels of differences of pelvic muscle strength before and after spontanous labor between stress urinary inconti-nence group and normal group. This research was done using analytic method with cross sectional design in 13 women with stress urinary incontinence, and 17 women with normal group. Subjects were collected in hospitals of Pariaman, Padang from May to December 2014. Examination of the pelvic floor muscle strength was performed with a perineometer. Differences between the mean difference in the strength of the pelvic floor muscles before and after spontaneous delivery between the two groups were analyzed using independent t test. The mean difference between the strength of the pelvic floor muscles before and after spontaneous labor in stress urinary incontinence group was larger than normal group (3.85 + 1.281 cmH2O vs 2,00 + 1.173 cmH2O, p = 0.000). The mean difference between the strength of the pelvic floor muscles before and after spontaneous labor in stress urinary incontinence group was significantly greater than the normal group.Keywords: Pelvic Floor Muscle, Urinary Incontinence, Spontaneous Labor